Electronic Waste Generation and Management in the Middle East and North Africa (MENA) Region: Algeria as a Case Study, ISSN 1520-6483 - Hamouda Karima; Adjroudi Rachid (2017)
Electronic waste (e-waste) is one of the fastest growing waste streams in the world. Notwithstanding increasing concern worldwide, e-waste has not yet been discussed in depth in the Middle East and North Africa (MENA) region. This study first reviews the literature regarding the estimation of e-waste in the MENA region. It then gives an estimate of the past and future trends in the generation of obsolete computers in Algeria. For this purpose, the study combines two models: the Carnegie Mellon model and the market supply (distribution delay) model. The Carnegie Mellon model offers the following options for obsolete computers and monitors: the device could be reused, stored, or discarded. The amounts of devices falling into each category were determined based on these options. The outcomes from the market supply (distribution delay) model show that high amounts of computer and monitor waste were registered for the period from 2014 to 2016.